Biomechanical approaches to language learning investigating the impact of kinesthetic activities on Japanese pronunciation and fluency - Luo, Junchao (Molecular & Cellular Biomechanics, 2024)
This study investigates the impact of biomechanics-based kinesthetic activities on Japanese pronunciation accuracy and speech fluency among intermediate learners. A quasi-experimental design was employed, with 50 participants randomly assigned to either an experimental group (n = 25) that engaged in biomechanical interventions or a control group (n = 25) receiving traditional language instruction. The experimental group participated in a 10-week program, incorporating articulation exercises, respiratory training, rhythmic gestures, and posture alignment aimed at optimizing speech production. Pronunciation accuracy and fluency were assessed before and after the intervention using standardized scoring rubrics and speech analysis software. The results indicate significant improvements in both pronunciation accuracy and fluency in the experimental group compared to the control group. Specifically, the experimental group showed a marked increase in pronunciation scores (from 2.8 to 4.1) and a higher speech rate (from 120 to 150 words per min) with fewer pauses (from 8 to 4 per min). Statistical analysis, including independent samples t-tests and one-way ANOVA, confirmed the effectiveness of the kinesthetic interventions, with post-hoc Tukey HSD tests revealing significant differences between the groups. The findings suggest that integrating biomechanics-based kinesthetic activities into language instruction can significantly enhance learners’ pronunciation and fluency, providing a more holistic approach to language acquisition. Future research should explore the long-term impact of these interventions and their applicability to other languages.